Behavioral Determinants of Switching to Arsenic-Safe Water Wells: An Analysis of a Randomized Controlled Trial of Health Education Interventions Coupled With Water Arsenic Testing. (February 2017) - George, Christine Marie; Inauen, Jennifer; Perin, Jamie; Tighe, Jennifer; Hasan, Khaled; Zheng, Yan
More than 100 million people globally are estimated to be exposed to arsenic in drinking water that exceeds the World Health Organization guideline of 10 µg/L. In an effort to develop and test a low-cost sustainable approach for water arsenic testing in Bangladesh, we conducted a randomized controlled trial which found arsenic educational interventions when combined with fee-based water arsenic testing programs led to nearly all households buying an arsenic test for their drinking water sources (93%) compared with only 53% when fee-based arsenic testing alone was offered. The aim of the present study was to build on the findings of this trial by investigating prospectively the psychological factors that were most strongly associated with switching to arsenic-safe wells in response to these interventions. Our theoretical framework was the RANAS (risk, attitude, norm, ability, and self-regulation) model of behavior change. In the multivariate logistic regression model of 285 baseline unsafe well users, switching to an arsenic-safe water source was significantly associated with increased instrumental attitude (odds ratio [OR] = 9.12; 95% confidence interval [CI] = [1.85, 45.00]), descriptive norm (OR = 34.02; 95% CI = [6.11, 189.45]), coping planning (OR = 11.59; 95% CI = [3.82, 35.19]), and commitment (OR = 10.78; 95% CI = [2.33, 49.99]). In addition, each additional minute from the nearest arsenic-safe drinking water source reduced the odds of switching to an arsenic-safe well by more than 10% (OR = 0.89; 95% CI = [0.87, 0.92]). Future arsenic mitigation programs should target these behavioral determinants of switching to arsenic-safe water sources.